Selection of Digital Filter for Microprocessor Protection Relays - Denis B. Solovev (Institute of Advanced Engineering and Science, 2018)
The article considers some issues related to replacement of electromechanical relays used for protection of power facilities with microprocessor relays. One of the urgent problems connected with implementation of microprocessor overcurrent protections is how to use current transducers other than usual current transformers and in particular Rogowski coils that become more and more widespread. In the article are compared twelve methods of synthesis of a digital filter basing on the analog prototype – second-order integrating filter. The bilinear filter and Boxer-Thaler filters are analyzed in respect to their use in microprocessor relays. Basing on the research results a technique for selection of parameters of digital integrating filters for microprocessor relays is proposed. Simulation results show that Boxer-Thaler and bilinear filters have better accuracy during transient current measurements than the analog filter. The study allows concluding that in many cases the digital second-order bilinear filter is the best choice for use in microprocessor relays.